2004
DOI: 10.1152/ajpheart.01140.2003
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning-mediated restoration of membrane dystrophin during reperfusion correlates with protection against contraction-induced myocardial injury

Abstract: Dystrophin is an integral membrane protein involved in the stabilization of the sarcolemmal membrane in cardiac muscle. We hypothesized that the loss of membrane dystrophin during ischemia and reperfusion is responsible for contractile force-induced myocardial injury and that cardioprotection afforded by ischemic preconditioning (IPC) is related to the preservation of membrane dystrophin. Isolated and perfused rat hearts were subjected to 30 min of global ischemia, followed by reperfusion with or without the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 46 publications
(45 reference statements)
3
41
0
2
Order By: Relevance
“…Several recent studies have indeed demonstrated that the intracellular ATP level is a critical determinant of the form of cell death. [17][18][19] Although our study was unable to evaluate ATP levels in individual myocytes undergoing apoptosis and oncosis because of the inherent difficulty in measuring ATP in individual myocytes, Terminella et al 25 found that the critical value of ATP required for completion of apoptotic signaling was 12-50% of the normal cellular ATP concentration. Provided that the average ∆ m in individual myocytes is proportional to the intracellular ATP level, the average TMRE uptake of myocytes undergoing apoptosis (31.9±1.8% of non-ischemic myocytes) observed in the present study is consistent with such a critical ATP concentration in determining the form of cell death.…”
Section: Discussionmentioning
confidence: 86%
“…Several recent studies have indeed demonstrated that the intracellular ATP level is a critical determinant of the form of cell death. [17][18][19] Although our study was unable to evaluate ATP levels in individual myocytes undergoing apoptosis and oncosis because of the inherent difficulty in measuring ATP in individual myocytes, Terminella et al 25 found that the critical value of ATP required for completion of apoptotic signaling was 12-50% of the normal cellular ATP concentration. Provided that the average ∆ m in individual myocytes is proportional to the intracellular ATP level, the average TMRE uptake of myocytes undergoing apoptosis (31.9±1.8% of non-ischemic myocytes) observed in the present study is consistent with such a critical ATP concentration in determining the form of cell death.…”
Section: Discussionmentioning
confidence: 86%
“…The isolated and buffer-perfused rat heart preparation was established as described previously, 23 and the heart was subjected to 30 min ischemia followed by 120 min reperfusion. IPost Figure 1.…”
Section: Animal Preparation and Perfusion Techniquementioning
confidence: 99%
“…23 During the stabilization period, a latex balloon was inserted into the left ventricle through the left atrium to measure the isovolumic LV function. The balloon was filled with saline solution to produce an LV end-diastolic pressure (LVEDP) of 5-10 mmHg at the baseline, and the balloon volume was kept constant throughout the experiment.…”
Section: Measurements Of Left Ventricular (Lv) Functionmentioning
confidence: 99%
See 2 more Smart Citations